Chromatin Immunoprecipitation in Chloroplasts. Issue 1 (25th January 2022) - Wang, Wenjie; Cheng, Lingling; Sun, Qianwen
Abstract: Chromatin is the genetic material assembled by nucleic acids (including DNA and RNA) and proteins. The biological functions of chromatin are highly dependent on the interaction between DNA (and/or RNA) and proteins that bind to it. Chromatin immunoprecipitation (ChIP) is a powerful technique for evaluating these interactions and has been widely used to characterize the functions of nuclear proteins. However, its application in identifying plant organellar chromatin‐binding proteins is lagging. This article describes the method for analyzing the association of chloroplast‐localized proteins with the chloroplast genome. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Chloroplast isolation Basic Protocol 2 : Crosslinking of DNA–Protein complexes Basic Protocol 3 : Chromatin isolation and preparation Support Protocol : Bead‐antibody complex preparation Basic Protocol 4 : Immunoprecipitation and washes Basic Protocol 5 : DNA preparation Basic Protocol 6 : Analysis of results